Analisis Lingkungan Internal dan Eksternal untuk Perencanaan Strategi Bisnis: Studi Kasus pada UMKM Cimol Bojot Aa Panyileukan - Dzilla Khoerunnisa; Rosiana Dewi; Layalia Auliaur Rahman; Ahmad Zhofaro Jawharul Fadl; Noval Wijaya; Siti Mardiana (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Micro, Small, and Medium Enterprises (SMEs) play an important role in the economy, including in the growing culinary sector. Cimol Bojot Aa, a culinary business focusing on selling cimol snacks, operates in a highly competitive market. This study aims to analyze the internal and external environments influencing the business strategy of the SME Cimol Bojot Aa. The methodology used includes SWOT and TOWS analysis, combining internal and external factor analysis to formulate business development strategies. Data were collected through interviews with the business owner, direct observation, and related document studies. The results show that Cimol Bojot Aa has strengths in unique products and competitive pricing, but faces challenges in marketing and financial management. Based on these findings, it is recommended that the business focus on strengthening digital marketing strategies and improving financial management for sustainable growth. This study provides practical recommendations for SME owners in planning adaptive and competitive business strategies in the culinary market.